Revestimentos comestíveis de misturas de polissacarídeos na Conservação pós-colheita de manga tommy atkins - Oliveira, Thiago Azevedo de (Universidade Federal Rural do Semi-Árido, 2017)
With the lack of information about the influence of coating of polysaccharide mixes on conservation of mangoes’ quality and knowing its positive effect on extending shelf life of vegetables, this present study aimed to evaluate the effect of cassava starch, chitosan, and pectin based coatings, on Tommy Atkins mangoes quality during storage. For this, three experiments were conducted: evaluating effects of coatings on respiratory activity, physicochemical quality, and sensorial quality, stored at 13º and 10ºC and 90±5% RH during 28, 35 and 42 days. Mango fruits for each experiment were collected at physiological maturity and transported to Laboratório de Tecnologia de Alimentos (lab) at UFERSA for cleaning, weighting, and identification, then undergone the respective treatment for each experiment and, stored for 28, 35 and 42 days, with evaluation interval of 3, 7 and 28 days. Experiments were conducted on surface response analysis and completly randomized design, in factorial scheme. Following analysis were made on fruits: Physiological loss, appearance, skin and pulp color, firmness, soluble solids level, pH, titratable acidity, SS/AT ratio, respiratory activity and sensorial analysis. Data were submitted to variance analysis with SISVAR software and compared by Tukey and Scott-Knott tests at 5% of probability. FE/QI coating was more efficient in controlling ripening of Tommy Atkins mangoes, permitting the extension of its shelf life in comparison to fruits from control treatment. The coating promoted less respiratory rate, less physiological loss and kept pulp color and firmness. Mangoes coated with FE/QI showed lower values for dehydration and spots, higher uniformity of color, bright, and flavor in the sensorial analysis, getting the highest scores of acceptance and purchase intention during storage. Application of cassava starch/chitosan was more efficient in reducing post-harvest deterioration, maintaining for longer period the sensorial quality of mangoes during refrigerated storage
Keywords: Mangifera indica L; Revestimentos comestíveis; Polissacarídeos; Conservação; Qualidade sensorial; Mangifera indica L; Edible coatings; Polysaccharide conservation; Sensorial quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA